Upaya Meningkatan Hasil Belajar Siswa pada Tema “Peduli Terhadap Makhluk Hidup” Melalui Model Pembelajaran Problem Based Learning di Kelas IV SD Negeri 168/X Pandan Sejahtera - Siska Ramayani (Journal on Education, 2021)
This study aims to disclose information and discuss Efforts to Improve Student Learning Outcomes on the Theme of Caring for Living Creatures through Problem Based Learning Models in Class IV SD Negeri 168/X Pandan Sejahtera. This research is included in the type of classroom action research (CAR). This research was carried out in this research was carried out at SD Negeri 168/X Pandan Sejahtera. The time of this research was carried out in the odd semester of the academic year 2021 - 2022, which began in October 2021. The subjects in this study were class IV students, totaling 16 people. The research procedure consisted of two cycles with four stages of research starting from planning, implementing, observing, and reflecting. Data collection in this study was carried out using observation sheets, learning outcomes test sheets, and documents. The data were analyzed using the percentage formula. The results of this study indicate that through use of Problem Based Learning Learning Model on the Theme of Caring for Living Creatures can improve student learning outcomes in grade IV SD Negeri 168/X Pandan Sejahtera which is marked by an increase from pre-cycle (31%), cycle I (56%), cycle II (94%).